2005
DOI: 10.1007/s11270-005-3023-6
|View full text |Cite
|
Sign up to set email alerts
|

Availability to Lettuce of Arsenic and Lead from Trace Element Fertilizers in Soil

Abstract: Some waste-derived trace element fertilizers may contain elevated amounts of arsenic (As) and/or lead (Pb), and the impact of their use on As and Pb accumulation in soil and uptake by plants should be investigated. This greenhouse study examined how increasing rates of an iron (IR) fertilizer, containing 4806 mg kg −1 of As, and a zinc fertilizer (G-Zn), containing 18080 mg kg −1 of Pb, and liming affected As and Pb availability and uptake by lettuce (Lactuca sativa L.) in a silt loam soil. Additions of As as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
(54 reference statements)
4
6
0
Order By: Relevance
“…In the 0-10 cm layer, an obvious effect of pH on the concentration of plant-available Zn was detected while no effect of liming was observed with Pb. These results were in accordance with other authors (Chowdhury et al 1997;Huang et al 2005;Száková et al 2007).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the 0-10 cm layer, an obvious effect of pH on the concentration of plant-available Zn was detected while no effect of liming was observed with Pb. These results were in accordance with other authors (Chowdhury et al 1997;Huang et al 2005;Száková et al 2007).…”
Section: Discussionsupporting
confidence: 94%
“…In the RGE, the effect of As present in basic slag combined with the enhanced mobility of As caused by the addition of phosphate fertilisers was apparent. Huang et al (2005) reported no significant changes in As mobility in limed soil, whereas in experiments published by Száková et al (2007) the mobile portion of As in limed soil tended to increase as in the RGE. There are many contradicting results that make it difficult to give exact explanations for these differences.…”
Section: Discussionmentioning
confidence: 78%
“…A low uptake of soil lead by the aboveground biomass of tested vegetables was apparent but a significantly increased Pb content in lettuce leaves at Chernozem and chard leaves at Fluvisol was observed (Table 5 and 6). A lower mobility and/or plantavailability of lead compared to other elements such as Cd and Zn was confirmed in this experiment as well as by Huang et al [35] and Sawidis et al [36]. The lead content in lettuce was variable by location and affected by individual soil physicochemical conditions, especially pH levels and clay content in the soils [12].…”
Section: Leadsupporting
confidence: 84%
“…Therefore, these leafy vegetable cultivars can be considered as a As excluder (Baker and Whiting, 2002), comprising avoidance of metal uptake and restriction of metal transport to the shoots. This is consistent with the results reported by Huang et al (2005) using lettuce and when compared with other plants such as Pteris vittata (Francesconi et al,2002), the As concentrations were high in the shoot (aboveground) than in root, also the TFs were greater than 1.0. Wei et al (2005) found that the exclusion of metals from shoot has been regarded as a metal tolerant strategy.…”
Section: The Important Factors Affecting As Uptake By Cultivarssupporting
confidence: 92%